Preparação e incorporação do substrato em atta sexdens rubropilosa forel, 1908 (Hymenoptera: formicidae) e morfofuncionalidade mandibular em espécies de atta - Silva, Laís Cristina da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Species of leaf - c utting ants of the genus Atta are important pests of agriculture and forestry Brazilian because they use plant material as substrate for the cultivation of your symbiotic fungus, thus requiring control methods to reduce the damage caused by their foraging activities. The most used are the toxic baits. The symbiotic association provides adequate nutritional constitution to the colony, the main food source for the larvae and important constituent of the diet of adult workers. The objectives of this study was observe the behavioral repertoire of Atta leaf cutter during preparation and incorporation of two different substrates, leaves and ant poison baits, as well as the participation of each caste involved in this process, stressing possible morphological diffe rences between the jaws of leaf - cutting ants grasses and dicots. For a detailed description of both jaws of the workers, anatomy and chemical composition of plant material species foraged by bisphaerica Atta and A. s. rubropilosa was prepared, as well as a n ethogram showing behavioral acts performed by workers' overalls, and generalist foragers of A. s. rubropilosa during processing and incorporation of two different substrates. It has verified that Atta species have similar morphology jaw. The difference w as observed just inside the grapes analyzed. Regarding the morphological description of the plant material foraged, results indicate that grasses have more lignified points, it can be inferred that their foraging and processing requires a greater effort of workers and could lead to differentiation in behavioral acts in their preparation and incorporation into the fungus garden . For the three castes found eight behavioral acts were recorded, regardless of substrate processed by workers ...

As es pécies de formigas cortadeiras do gênero Atta são consideradas importantes pragas da agricultura e silvicultura brasileira, pois utilizam material vegetal como substrato para o cultivo de seu fungo simbionte, exigindo assim métodos de controle para reduzir os danos causados por sua atividade forrageira, sendo o uso de iscas tóxicas um dos mais utilizados. A associação simbiótica fornece uma constituição nutricional adequada à colônia, sendo a principal fonte alimentar para as larvas e constituinte important e da alimentação das operárias adultas. O s objetivo s deste estudo foi observar o repertório comportamental de Atta sexdens rubropilosa durante a preparação e incorporação de dois substratos diferentes, folhas e iscas granuladas , bem como a participação de cada casta envolvida nesse processo, destacando possíveis diferenças morfológicas entre as mandíbulas de formigas cortadeiras de gramíneas e dicotiledôneas. Para tanto uma descrição detalhada das mandíbulas das operárias, da anatomia e da composição químic a do material vegetal forrageado pelas espécies Atta b isphaerica e A. s. rubropilosa foi elaborada, assim como um etograma evidenciando os atos comportamentais executados pelas operarias jardineiras, generalistas e forrageiras da espécie A. s . rubropilosa, durante o processamento e incorporação de dois diferentes substratos. Verificou - se que as espécies de Atta apresentam morfologia da mandíbula semelhantes, sendo observada diferença apenas dentro das castas analisadas. Em relação à descrição morfologica do material vegetal forrageado os resultados indicam que as gramíneas apresentam mais pontos lignificados, permitindo inferir que seu forrageamento e processamento exige um maior esforço das operárias e poderia levar à diferenciação nos atos comportamentais na sua preparação e incorporação no jardim de fungo. Para as 3 castas ...
Keywords: Himenoptero; Substratos; Silicio; Mandíbula; Hymenoptera